The effects of the oil price and temperature on food inflation in Latin America - Kose, Nezir; Unal, Emre (Springer, 2024)
The impacts on food prices of temperature, the oil price, the exchange rate and wages in the agricultural industry were examined via a structural vector autoregression model and panel Granger causality test, using monthly data between January 2003 and December 2020 for Latin American countries. The paper concerns how much the determinants affect food prices. Empirical findings show that the oil price and temperature can be significant factors for reducing food inflation. According to the result of variance decomposition, in general, a considerable part of food inflation was explained by the exchange rate, but its effect did not show any significant change in the long term. The impacts of the oil price and temperature were limited in the early months, but they created larger changes over time. Impulse response function and the Granger causality test also indicated that exchange rate was a crucial dynamic in explaining food inflation in all countries except Ecuador. This country successfully mitigated the negative effect of the exchange rate, but the oil price and temperature had an impact on food inflation. All results indicate that both monetary and fiscal policies are essential to control food prices. These countries can accomplish this by conventional policies or by radical institutional changes. Nevertheless, the oil price and temperature are external dynamics, and crucial in creating alternative policies to control food inflation.
Keywords: Food prices; Oil price; Temperature; Structural VAR